2011
DOI: 10.1016/j.bbabio.2010.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Dual localization of plant glutamate receptor AtGLR3.4 to plastids and plasmamembrane

Abstract: Bioinformatic approaches have allowed the identification in Arabidopsis thaliana of twenty genes encoding for homologues of animal ionotropic glutamate receptors (iGLRs). Some of these putative receptor proteins, grouped into three subfamilies, have been located to the plasmamembrane, but their possible location in organelles has not been investigated so far. In the present work we provide multiple evidence for the plastid localization of a glutamate receptor, AtGLR3.4, in Arabidopsis and tobacco. Biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 56 publications
1
47
0
Order By: Relevance
“…1D). No evidence of chloroplast localization of GLR3.4 reported in a study that also reported plasma membrane localization (Teardo et al, 2011) was detected, though intense chlorophyll fluorescence could have masked a weak GFP signal.…”
Section: Subcellular Localization Of Glr34 Expressed In Mammalian Anmentioning
confidence: 90%
“…1D). No evidence of chloroplast localization of GLR3.4 reported in a study that also reported plasma membrane localization (Teardo et al, 2011) was detected, though intense chlorophyll fluorescence could have masked a weak GFP signal.…”
Section: Subcellular Localization Of Glr34 Expressed In Mammalian Anmentioning
confidence: 90%
“…Although both of these plasma membrane proteins reside at the sieve plate in roots, their activities ultimately manifest in the pericycle with a regulatory effect on the production of lateral root primordia (Vincill et al, 2013). The finding that AtGLR3.4 can reside in the chloroplast (Teardo et al, 2011), although not confirmed by Vincill et al (2012), raises further opportunities and challenges for the GLR community. The question remains whether the concentrations of amino acids used in assays would occur in planta (Vincill et al, 2012); many studies use concentrations of ligand higher than would be expected outside of cells.…”
Section: Glrs: More Evidence For Calcium Channelsmentioning
confidence: 98%
“…As mentioned earlier, there are now indications of CNGC residence at the tonoplast, GLR residence at the chloroplast, and MSL residence in chloroplasts (Teardo et al, 2011;Veley et al, 2012;Yuen and Christopher, 2013). The chloroplast protein translocon TIC complex conducts K + in PLB, and its capacity for Ca 2+ conduction now needs to be explored (Kikuchi et al, 2013).…”
Section: Endomembranes: Tpc1 Remains Controversial and New Insight Fmentioning
confidence: 99%
“…Therefore, integration into the plasma membrane seems to be likely (Lam et al 1998;Chiu et al 1999;Nagata 2004;Teardo et al 2010). Besides the signal sequences for the secretory pathway, mitochondrial and chloroplast targeting sequences can be found (Teardo et al 2010(Teardo et al , 2011. When looking at clade III in A. thaliana, four of seven receptors (AtGLR3.1, 3.2, 3.6 and AtGLR3.7) are supposed to enter the secretory pathway while the three others (AtGLR3.3, 3.4 and 3.5) contain multiple targeting sequences (Teardo et al 2010(Teardo et al , 2011.…”
Section: Subcellular Localisationmentioning
confidence: 99%